Fungal and Bacterial Diversity Patterns of Two Diversity Levels Retrieved From a Late Decaying Fagus sylvatica Under Two Temperature Regimes - Muszynski, Sarah; Maurer, Florian; Henjes, Sina; Horn, Marcus A.; Noll, Matthias (Frontiers in Microbiology, 2021)
Environmental fluctuations are a common occurrence in an ecosystem, which have an impact on organismic diversity and associated ecosystem services. The aim of this study was to investigate how a natural and a species richness-reduced wood decaying community diversity were capable of decomposing Fagus sylvatica dead wood under a constant and a fluctuating temperature regime. Therefore, microcosms with both diversity levels (natural and species richness-reduced) were prepared and incubated for eight weeks under both temperature regimes. Relative wood mass loss, wood pH, carbon dioxide and methane emissions, as well as fungal and bacterial community compositions in terms of Simpson`s diversity, richness and evenness were investigated. Community interactions patterns and co-occurrence networks were calculated. Community composition was affected by temperature regime and natural diversity caused significantly higher mass loss than richness-reduced diversity. In contrast, richness-reduced diversity increased wood pH. The bacterial community composition was less affected by richness reduction and temperature regimes than the fungal community composition. Microbial interaction patterns showed more mutual exclusions in richness-reduced compared to natrual diversity as the reduction mainly reduced abundant fungal species and disintegrated previous interaction patterns. Microbial communities reassembled in richness-reduced diversity with a focus on nitrate reducing and dinitrogen-fixing bacteria as connectors in the network, indicating their high relevance to reestablish ecosystem functions. Therefore, a stochastic richness reduction was followed by functional trait based reassembly to recover previous ecosystem productivity.